KINERJA PEGAWAI HONORER PADA BAGIAN AKADEMIK UNIVIVERSITAS SAM RATULANGI MANADO - PELEALU, CHENDY (Sam Ratulangi University, 2017)
AbstractThe research aims to know and analyze the performance of honorary employees in the Academic Divisionof Sam Ratulangi University Manado University. The study was conducted qualitatively. The samplingtechnique used by the researcher is purposive sampling. Informants in this study set eight people. Asinformants are sub-divisions of two persons, head of one person, and five students. The focus of the studyis the performance indicators, namely: Quality of Work (Quality of Work), Promptness, Initiative(Initiative), Capability (Capability), and Communication (Communication). Based on the results of theresearch, that the quality of work, accuracy, initiative, ability, and communication of honorary employeesin the academic section of Sam Ratulangi University Manado in performing the task quite well. In general,honorary workers are educated graduates and understand how to use the computer. Although still foundthe results of work, is still not good, this is due to the many jobs faced.Keywords: Employee honorary, performance, quality of work (quality of work), promptness, initiative,capability, and communication.